2021
DOI: 10.1007/s10854-021-05870-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and magnetic properties of nanostructured Ag-substituted Co-Zn ferrites: insights on anticancer and antiproliferative activities

Abstract: Magnetic spinel ferrite nanoparticles possess high scientific attention for the researchers attributed to its broad area for biomedicine purposes, comprising cancer magnetic hyperthermia and targeted drug delivery. Herein, we report the ultrasound irritation assisted the sol-gel method for the spinel Zn 0.5 Co 0.5x Ag 2x Fe 2 O 4 (x = 0.00, 0.10, 0.20, and 0.30) nanoparticles (NPs) synthesis. The Rietveld refinement patterns revealed the successful synthesis of the cubic structure Zn 0.5 Co 0.5-x Ag 2x Fe 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 79 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…Raised ROS levels can induce mitochondrial malfunction, DNA damage, and protein damage in the cells, leading to the suppression of cell growth and eventually cell death . All these data clearly revealed that the cytotoxicity of Zn ferrite NPs was dependent on concentration and exposure period, as has been reported in earlier investigations. The Zn ferrite NPs were established to be expressively more cytotoxic to HSF-1184 cells as compared to PEG@Zn ferrite NPs, which might be linked with the inherent anticancer characteristic of Zn ferrite NPs . In addition, cells treated with PEG@Zn ferrite NPs acquired a considerable viability of approximately 100% at 600 μg/mL concentration and 80% at 900 μg/mL concentration.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Raised ROS levels can induce mitochondrial malfunction, DNA damage, and protein damage in the cells, leading to the suppression of cell growth and eventually cell death . All these data clearly revealed that the cytotoxicity of Zn ferrite NPs was dependent on concentration and exposure period, as has been reported in earlier investigations. The Zn ferrite NPs were established to be expressively more cytotoxic to HSF-1184 cells as compared to PEG@Zn ferrite NPs, which might be linked with the inherent anticancer characteristic of Zn ferrite NPs . In addition, cells treated with PEG@Zn ferrite NPs acquired a considerable viability of approximately 100% at 600 μg/mL concentration and 80% at 900 μg/mL concentration.…”
Section: Methodssupporting
confidence: 63%
“…80−82 The Zn ferrite NPs were established to be expressively more cytotoxic to HSF-1184 cells as compared to PEG@ Zn ferrite NPs, which might be linked with the inherent anticancer characteristic of Zn ferrite NPs. 83 In addition, cells treated with PEG@Zn ferrite NPs acquired a considerable viability of approximately 100% at 600 μg/mL concentration and 80% at 900 μg/mL concentration. These results suggest that the biocompatibility of Zn ferrite NPs was significantly enhanced when coated with PEG, as reported elsewhere.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Each sample and control were analyzed in triplicate in three separate tests. The percentage growth (%) of viable cells that were subjected to various treatments was determined using the following calculation method [33][34][35][36][37] :…”
Section: Characterization Techniquesmentioning
confidence: 99%